USING DYNAMIC PRE-ACTIVATION OF STEEL SURFACES FOR NITRIDING INTENSIFICATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The article considers the possibility of pre-activation of the steel surface before nitriding. A complex dynamic method of material activation with a high-speed flow of powder particles (super deep penetration) was used. To exclude the influence of alloying elements, low-carbon steel (2% wt. C) was chosen as the initial material. Powders of NaF (> 250 μm) and Pb (